Ruthless Web Scraping for Data Science - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to ruthlessly scrape data using APIs you discover as well as cut and paste. Topics include: * Business Analytics * Data Science * Google Colab * Jupyter * Scraping * Cut and Paste * Google Sheets * Cleaning Data * Using Pandas with found data * Using the Twitter and Pandas API.